The East European financial crisis - Anders Åslund (Center for Social and Economic Research (CASE), 2009)
This paper discusses the global financial crisis of 2008/9 in thirteen countries, the ten new EU members that previously were communist and the three countries of Western former Soviet Union. Their problems were excessive current account deficits and private foreign debt, currency mismatches, and high inflation, while public finances were in good shape. The dominant cause was fixed exchange rates. Many lessons can be drawn from this crisis. A dollar peg makes no sense in this part of the world. The five currency boards in the region have lacked credibility. By contrast, inflation targeting has worked eminently. The euro has proven credible both in the countries that officially adopted it and in the countries that adopted it unilaterally. With the exception of Hungary, all the countries in the region have displayed decent fiscal policies. No government should accept large domestic loans in foreign currency and they can be regulated away. The IMF has successfully returned to the original Washington consensus with relatively few conditions: a reasonable budget balance and a realistic exchange rate policy, while focusing more on bank restructuring. The most controversial issue is the role of the ECB. The ECB should facilitate the accession of willing EU members to the euro by relaxing the ERM II conditions.
Keywords: B22; 330; Financial crisis; macroeconomics; exchange rate policy; Eastern Europe; transition; Finanzkrise; Geldpolitik; Inflationssteuerung; Wechselkurspolitik; Eurozone; Euro; Internationale Finanzhilfe; EU-Mitgliedschaft; Weißrussland; Ukraine; Moldawien